Sexual Perceptions among People Aged 45 years, Association of Reproductive Health and Socio-Demographic Factors in Klang Valley, Malaysia - Latiffah Latiff; Hanachi Parichehr (Tehran University of Medical Sciences, 2008)
Objective: The objective of this research was to study the sexual perception and practices among people aged 45 years and above and the associated socio-demographic factors. Materials and methods: A cross sectional study was done on 473 middle aged and elderly people living in Klang Valley in 2005. They were married and literate.  Data were collected by means of face to face interview using structured questionnaires and were analyzed using SPSS software. Logistic regression was used and p<0.05 was considered for statistical significance. Results: The mean age of the respondents was 54.36 ± 7.91 years and majority of them were in age group of 50-59yrs (41.25%) and 53.5 % were male. The ethnic distribution was 50.1% Malay, 23.3% Chinese and 26.6% Indians. Most of the  (61 %) reported that they were healthy as compared to 39% who suffered at least from a major medical problem. Only 17.1% of respondents admitted that they had sexual problems and out of these 32% sought various types of treatment. There was a  significant difference between satisfaction with sexual intercourse and gender, ethnicity, age, who initiated the sexual intercourse and presence of sexual problem. Conclusion: The findings indicate that older people present as wide a variety of sexual problem areas as younger individuals. Accurate information about sexuality in later life will enable professionals to better provide a desirable environment.